Absolute distance measurement based on spectral interferometry using femtosecond optical frequency comb. (September 2019) - Tang, Guoqing; Qu, Xinghua; Zhang, Fumin; Zhao, Xianyu; Peng, Bo
Highlights: Based on the spectral interferometry, a high-accuracy and robust absolute distance measurement method was demonstrated for arbitrary distance using the femtosecond optical frequency comb. The system gives a resolution of better than 30 µm in a range up to 70 m. Due to the nearly all-fiber and well-designed measurement setup, the presented system is high precision, robust and compact, as well as cheap for only one mode-locked comb. A high precision and robust phase unwrapping method was proposed with the phase demodulation of the signal envelops in a Hilbert way (PDSEH). And it reveals a single-point stability with a measurement standard deviation of ∼75 nm in a range of 70 m. Compared with the classical filtered Fourier transform phase unwrapping method, the non-filtered and differential PDSEH shows well robustness in the measurements for arbitrary distance, yielding a precision of 3.1 × 10 – 7 in relative. Abstract: We demonstrated an absolute distance measurement method based on the frequency folding effect using the spectral interferometry of femtosecond optical frequency comb. And the investigation was carried out on the ranging accuracy influence of the phase noise in the traditional complicated phase unwrapping method via band-pass filter and Fourier Transform. To reduce the effects of the phase noise, we proposed the non-filtered and differential envelop phase demodulation method, and its robustness was illustrated with a standard deviation of 75 nm for the stability of single point measurements. Further, through the extension of the non-ambiguity range, we achieved a resolution of better than 30 µm in a long distance measurements range of 70 m, yielding a relative precision of 3.1 × 10 −7 .